ANALYSIS OF SURVEY RESULTS ON COMMUNICATION, INFORMATION, AND EDUCATION MEDIA IN KERTOSARI VILLAGE - Ainursavitri, Ericha; Fitriyah, Nurul (HEARTY, 2025)
Health is a condition that enables individuals to live to their full potential. The Field Work Practice (PKL) activities use a descriptive approach, which is an activity that describes or outlines the picture of a health problem. In this case, the issue addressed is Non-Communicable Diseases (NCDs). Kertosari Village is one of the villages located in the Babadan District, Ponorogo Regency, East Java. The method of Problem identification based on secondary data found that there are 10 priority diseases in Kertosari Village, with hypertension being the main concern. Problem identification based on primary data was conducted through Focus Group Discussions, In-Depth Interviews, and questionnaire collection. The results was found that the residents of Kertosari Village have a good level of knowledge (54.55%), but the community's attitude is assessed as less favorable (62.12%). Alternative solutions were sought using the MEER system, and priority solutions were found, including the creation of hypertension-friendly recipes, education related to hypertension, cooking demonstrations, and training on digital-based data recording and reporting. Evaluation of activities is carried out after the program is implemented, including Pre-Test, Post-Test, and testimonials about the media.